Validation of Cefazolin as Initial Antibiotic for First Upper Urinary Tract Infection in Children - Yoshifusa Abe MD, PhD; Hitomi Wakabayashi; Yasuha Ogawa; Ayano Machida; Mio Endo; Tetsuro Tamai MD; Shunsuke Sakurai MD, PhD; Satoshi Hibino MD, PhD; Takeshi Mikawa MD; Yoshitaka Watanabe MD, PhD; Kazuhisa Ugajin ICMT; Kunihiko Fukuchi MD, PhD; et al. (SAGE Publishing, 2016)
To validate the policy of administering cefazolin (CEZ) as a first-line antibiotic to children who are hospitalized with their first febrile urinary tract infection (UTI), we evaluated microbial susceptibility to CEZ and the efficacy of CEZ. The 75 enrolled children with febrile UTI were initially treated with CEZ. Switching CEZ was not required in 84% of the patients. The median fever duration, prevalence of bacteremia, prevalence of UTI caused by extended-spectrum β-lactamase (ESBL)-producing Escherichia coli , and median duration of hospitalization were significantly higher in the CEZ-ineffective group. The risks of vesicoureteral reflux, indication of operation, and renal scarring are not increased, even when CEZ is ineffective as a first-line antibiotic. CEZ is effective in more than 80% of pediatric patients with their first febrile UTI, but it should be switched to appropriate antibiotics considering sepsis or the ESBL-producing Enterobacteriaceae pathogen, when fever does not improve within 72 hours.